A case study on English language learners’ task-based interaction and avatar identities in Second Life: A mixed-methods design - Chen, Julian (Research-publishing.net, 2014)
English as a foreign language (EFL) learners’ language use in 3-D virtual environments is a vibrant avenue that still deserves more research attention in the field of CALL. To contribute research and pedagogical implications to the current Second Life (SL) literature, this study aims to examine EFL adult learners’ use of communication strategies during task-driven, voice-based negotiation, as well as to explore their avatar identities during their language practices in a task-based virtual course in SL. Operationalized by task-based interaction, quantitative results show that confirmation checks, clarification requests and comprehension checks are the most frequently used strategies. The interrelationship among task types, negotiation and strategy use is also established –jigsaw task prompts the most instances of negotiation and strategy use. Qualitative results drawn from triangulation of multiple data sources reveal that SL is endorsed as a promising learning environment owing to its simulated immersion, augmented reality, tele/co-presence and masked identities via avatars. This study demonstrates that implementation of task-based instruction can be maximized by 3-D simulated features in SL. It also implicates that 1) two-way directed tasks with convergent and single-outcome conditions will stimulate more cognitive and linguistic processes of negotiation involving interactional modifications, and 2) avatar identities can boost EFL learners’ sense of self-image and confidence.